Changes in physicochemical properties of chitin at developmental stages (larvae, pupa and adult) of Vespa crabro (wasp). (10th July 2016) - Kaya, Murat; Sofi, Karwan; Sargin, Idris; Mujtaba, Muhammad
Highlights: Relation of chitin content of an insect ( Vespa crabro ) to its developmental stages. How characteristics of chitin change as the insect grows. Dramatic increase in chitin storage of the insect in pupa stage. Increase in diversification of surface morphology by the developmental stages. Abstract: It is already known that chitin in a single organism can exhibit huge differences depending on the functions it serves in different body parts, but the alterations in the characteristics of chitin in course of developmental stages of an organism still remain unknown. This study presents findings on how chitin matrix is changing physicochemically through discrete morphological stages – larva, pupa and adult – of an insect ( Vespa crabro ). Chitin content of the organisms were found to increase gradually as the organism grew; 2.1, 6.2 and 10.3%, with a dramatic increase in chitin deposition (nearly 3 folds) during the instar from larva to pupa. Enzymatic digestion test demonstrated that chitin isolates were close to pure. Chitin isolates were also subjected to thermal pyrolysis and no variations were observed in the thermal stability of the samples. However, it was observed that surface characteristics of chitin changed greatly as the insect grew.